Penyuluhan Menghadapi Era New Normal Covid – 19 dan Bisnis di Masa Less Contact Economy di Rumah Baca Komunitas Yogyakarta - Annisa Khumaira; Fitri Maulidah Rahmawati (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2023)
Abstract Since Covid-19 was declared a global pandemic, many changes have occurred in people's social life. The need to maintain physical distance has made an impact in various fields, one of which is that there is a recession in various countries, and Indonesia gives a signal that it will experience this, indicated by the country's gross income of -5.32%. In dealing with this, the government has imposed a "new normal", namely the return of community activities by implementing health protocols. Rumah Baca Komunitas (RBK), as a literacy community in Yogyakarta, its members need counseling on health protocols that are implemented during the new normal and business strategies during the occurrence of social restrictions. The results of the evaluation show that the participants feel the impact of social restrictions from an economic perspective. According to the participants, the material presented was useful for the participants to be disciplined in implementing health protocols and always have income despite limited access.